America and World Power - Adams, James Truslow (Chares Scribner's & Sons New York, 1933)
The First 4 volumes of this set chronicle the history of the United States from discovery to the Great Depression and election of FDR. The book titles are: 1. The Rise of the Union 2. A Half Century of Expansion 3. Civil War and Aftermath 4. America and World Power Volumes V-VII are a continuation of Adams' work through annual records from 1933-1963: 5. The Record of 1933-1941 6. The Record of 1942-1948 7. The Record of 1949-1963 Each volume contains plentiful black-and-white illustrations, political cartoons, documents, pamphlets, etc. The final pages of each volume are devoted to picturing the theme of that particular volume, depicting many typical scenes, outstanding personalities, and some of the most conspicuous representations of our architectural imagination - a veritable panorama of American life.
Descriptive letterpress on versos facing some of the plates. Also published under title: History of the United States.
Keywords: History -- American; History